Edmodo E-Learning Analysis using End-User Computing Satisfaction Method (Case Study: Senior High School 1 Sampang) - Nur Rachmah, Khusnia; Nashirul Haq, Ahmad; Assobarry, Nur Hasan; Nanda Sabila, Fariza; Mardi Suryanto, Tri Lathif (International Journal of Computer, Network Security and Information System, 2021)
The development of information technology that continues to grow in all aspects of life which makes human work more efficient and effective. The current COVID-19 pandemic is one of the conditions in which people's activities are hindered and limited in their daily activities. The application of Information Technology is a solution that can be applied for the sustainability of community activities in the midst of this pandemic, one of which is the education sector. Edmodo's E-Learning system is one of the most widely used e-learning systems for the teaching and learning process. The application of e-learning certainly changes the way students learn from offline to online. EUCS (end-user computing satisfaction) is one of the methods used to analyze user satisfaction of an information system, where this method has 5 variables, namely content, accuracy, format, ease of use, and timeliness. The case study of Senior High School 1 Sampang will be the object of this research, where the EUCS method is used to measure the satisfaction of end users of the Edmodo E-Learning system. Data was collected by distributing questionnaires to active students at Senior High School 1 Sampang by obtaining a sample of 80 respondents. From the results of the research conducted, it was found that the EUCS method can be applied to the Edmodo E-Learning system at Senior High School 1 Sampang because the data obtained from the respondents was declared valid and reliable so that it can be relied upon in measuring end user satisfaction with the Edmodo E-learning system, while the factors - the factors of the EUCS method that affect the satisfaction of the end user of the Edmodo E-Learning system at Srnior High School 1 Sampang are the content and accuracy factors.